Multiobjective Three-Level Supply Chain Management Problem Under Uncertainty Using Gravitational Search Algorithm - Mojtaba Lati; Hassan Ali Aghajani; Mohammad Reza Lotfi (Discrete Dynamics in Nature and Society)
A supply chain is a set of resources, facilities, customers, products, and methods of inventory control, purchasing, and distribution. Every manufacturer or distributor has a subset of the supply chain that they have to manage and implement beneficially and efficiently for their survival and growth. Therefore, the production and delivery of products in the proper amounts and at the right time is as important as minimizing costs as well as customer satisfaction. Considering these reasons, supply chain network optimization includes decisions from many different aspects. In this study, a single-product three-level supply chain with manufacturer-customer loops is considered that customer demand, percentage of returned products from customers, and delivery time from manufacturers to customers are considered as fuzzy variables with uncertainty. Simultaneously considering the issues of selecting suppliers and distributors and determining the effective customers in the system is under uncertainty. This project aims to provide a model that, in addition to integrating the conflicting goals of the loops, also increases the number of uncertain parameters of the model. Therefore, the objectives of the proposed model are to maximize product quality; minimize total cost; minimize delivery time from distributors to customers; and maximize revenue from selling products to customers.